The collision of particles in granular systems - Brilliantov, Nikolai; Spahn, Frank; Hertzsch, Jan-Martin; Pöschel, Thorsten (Physica A-Statistical Mechanics and Its Applications, 1996)
Collisions between granular particles are irreversible processes which cause dissipation of mechanical energy by fragmentation or heating of the colliders. The knowledge of these phenomena is essential for the understanding of the behaviour of complex systems of granular particles. We have developed a model for inelastic collisions of granular particles and calculated the velocity restitution coefficients, which describe all possible collisions in the system. The knowledge of these coefficients allows for event-driven many-particle simulations which cannot be performed in the frame of molecular dynamics. This approach has the advantage that very large particle numbers can be treated which are necessary for the understanding of intrinsic large-scale phenomena in granular systems.